2014
DOI: 10.1007/s00468-014-1049-3
|View full text |Cite|
|
Sign up to set email alerts
|

Interannual variations in primary and secondary growth of Nothofagus pumilio and their relationships with climate

Abstract: Key messageThe aim of this study is to evaluate the relationships between primary and secondary growth as well as the influences of climate variations on both types of growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…At high-elevations, the precipitation falling mainly as snow in July, a thick snowpack could not only provide snowmelt water but also protect soil from frost, making melt water infiltration into the soil possible. Therefore, the positive correlation between ring-width and precipitation in July is likely induced by the positive effect of the snow pack accumulation and the consequent soil water recharge (Magnin et al, 2014;Villalba et al, 1997). Consistently, the VS-lite model simulates a dominant control of tree-growth by moisture availability.…”
Section: Patterns Of Tree-ring Growth Along the Moisture Gradientmentioning
confidence: 91%
“…At high-elevations, the precipitation falling mainly as snow in July, a thick snowpack could not only provide snowmelt water but also protect soil from frost, making melt water infiltration into the soil possible. Therefore, the positive correlation between ring-width and precipitation in July is likely induced by the positive effect of the snow pack accumulation and the consequent soil water recharge (Magnin et al, 2014;Villalba et al, 1997). Consistently, the VS-lite model simulates a dominant control of tree-growth by moisture availability.…”
Section: Patterns Of Tree-ring Growth Along the Moisture Gradientmentioning
confidence: 91%
“…Climate change during recent decades has been found to play a role in altering forest composition and structure on regional as well as global scales (Allen et al 2010;Anderegg et al 2013;Magnin et al 2014). Fritts (1976) reported that tree growth is more affected by mean temperature close to the treeline than that at low elevations, where precipitation is more influential.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, such observations were not available for N. pumilio, and therefore the parameterization obtained for the GPP of P. mariana was also used for the western Argentinian sites but constraining the simulations with phenological observations extracted from the literature. For example, to respect the annual cycle of the leaf area index (LAI) for N. pumilio (Magnin et al, 2014;Rusch, 1993), in MAIDENiso we used a seasonal LAI annual cycle with a development of leaves (LAI increase) between October and November, a maximum LAI (set at 5 leaf area/ground area) from November to April, a decreasing LAI (leaf fall) between April and May, and finally a leafless period (null LAI) from June to September (Magnin et al, 2014;Rusch, 1993). Furthermore, based on the finding that δ 18 O TR annual time series were more correlated with climate variables of specific months of the growing season (Lavergne et al, 2016), we also computed δ 18 O TR annual values by weighting the δ 18 O TR daily values (Eq.…”
Section: Modelling Oxygen Isotopes In Tree Ring Cellulose With Maidenisomentioning
confidence: 99%